Cooking skills in undergraduates: Results of a multicenter Brazilian cross-sectional study - José Douglas Bernardino Domingos; Manuela Mika Jomori; Erika Paula Silva Freitas; Eva Débora de Oliveira Andrade; Rafaela Nayara da Costa Pelonha; Ana Paula de Bulhões Vieira; Thaysa Barbosa Cavalcante Brandão; Bruna Merten Padilha; Thais Souza Passos; Bruna Leal Lima Maciel (PLoS ONE, 2026)
Understanding university students’ cooking skills is essential for guiding actions aimed at improving dietary quality through culinary practices. The university environment offers a unique opportunity to promote health and quality of life among young adults, making the development of cooking-related competencies a valuable strategy for fostering healthy eating habits. This study aimed to analyze the cooking skills of undergraduate students. This is a cross-sectional study, with data collected between October 2020 and March 2021, with undergraduate students (n = 3138) from 4 public universities in Brazil. The Brazilian Questionnaire for the Assessment of Cooking Skills and Healthy Eating was used to collect data. Logistic regressions were used to assess the associations of cooking skills with socioeconomic variables. Of the total students, 72.6% were female, with a median age of 22 (20–26) years, and 68.0% demonstrated high cooking skills. High cooking skills were associated with female students, those who had learned how to cook through classes, courses, or school, as well as those who had acquired skills through self-directed methods, such as the internet, cookbooks, or TV programs.. Logistic regression analysis showed that across all universities, students with high knowledge of culinary terms and techniques and high availability and accessibility of fruits and vegetables were less likely to have low or intermediate culinary skills. Therefore, interventions focused on cooking skills in the study population should primarily target male students, encouraging undergraduates to learn how to cook independently, enhancing the availability and accessibility of fruits and vegetables, and increasing their knowledge of cooking terms and techniques.